Accountability and Financial Management of Mosques Based on ISAK 35 Concerning Financial Reporting of Non-Profit Organizations: Case Study at Al-Ikhlas Mosque - Siregar, Dhetia Putri; Soemitra, Andri; Nasution, Juliana (PT. Riset Press International, 2023)
This study aims to find out how accountability for financial management exists at the Al-Ikhlas mosque and to find out how it conforms to ISAK 35 regarding financial reporting of non-profit organizations. The method used in this research is descriptive qualitative research method. Data collection techniques used are observation, interviews, and documentation. According to ISAK 35, the financial statements of non-profit entities include statements of financial position, statements of comprehensive income, statements of cash flows and notes to financial statements. With good cash management, we can provide information to donors and other interested parties. The results of this study indicate that financial management at the Al-Ikhlas Mosque is still not in accordance with ISAK 35 standards, and the recording carried out by mosque administrators is still simple, namely recording income and expenses which are presented every Friday manually. The accountability process, which in this case is the process of disclosing to the congregation, is still not maximally detailed, only conveying the amount of income and expenses without clear details. Even so, the mosque parties have tried to make the best possible disclosure. This is because the management of the mosque does not know the financial recording system based on ISAK 35.